Catholic-Protestant Wage Differentials in Northern Ireland 2011: A Re-examination with Newly Available Data - Gillespie, Andrew; McVicar, Duncan; Rowland, Neil; Shuttleworth, Ian (The Economic and Social Review, 2024)
Despite an extensive literature on Catholic-Protestant unemployment differentials in Northern Ireland, little is known about wage differentials. This paper provides new evidence using the Earnings and Employees Study for 2011. We find no evidence of an overall Catholic wage penalty, with unadjusted and adjusted differentials no larger than 1.4 log per cent and statistically insignificant. Slightly larger differentials are found in some models for men, 50+ workers, and private sector workers, but again these are statistically indistinguishable from zero. Similar data linkages for 2001 and 1991 would enrich our understanding of the period when other measurable labour market disparities were wider.